Advancing Regional Climate Education - Sonia Ben Jaafar; Joe Y. Battikh (Fiker Institute, 2023)
Undoubtedly, climate change has had, and continues to have, a significant impact on West Asia and North Africa, making it one of the most affected regions in the world.1 According to the Sixth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) published this year, the region is already experiencing increased temperatures and more frequent heat waves. By 2040, these effects are estimated to worsen, with changes in precipitation patterns leading to an increase in water scarcity,  droughts, and desertification.2 In this pursuit, advancing regional climate education will be vital to maximizing economic growth and development potential through effective adaptation strategies. These include expanding investments in carbon-free energies, such as solar, wind, green hydrogen, and nuclear energy, leveraging new technologies, and integrating the tourism sector as a key player in the process.